تاريخ نشأة اللغة العربية وتطورها - Ediyani, Muhammad (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2019)
Arabic is the language of the tribes that inhabited the peninsula from Yemen to the Levant to the race and the borders of Palestine and Sana to reach their purposes, which is one of the Semitic languages, and the subject of the emergence of language of the subjects addressed by the researchers of old and recent, and expanded in them a lot and their work that some opinions, The most important of these are: humility and terminology, and language inspired by God. The first person was taught the names of everything (arrest), and the language was born cumulatively subject to the factor of space-time and human need. After the advent of Islam, the Arabic language evolved with the decline of the Holy Quran, because the Arabic language before the descent of the Qur'an was classified into poetry and prose. When the Quran came down, the linguistic expressions in the three Arabic languages became Quran, poetry and prose. There is no doubt that the Arabic language reached the height of its glory and rose in the era of Islam because it became part of religion, and in the era of prophecy and the origin of Islam, people take care of Arabic a lot and are keen on it because it is the language of the Koran and religion and the true and faithful messenger. Other factors affecting the development of Arabic are political, social and cultural factors.